Introduction: Think tanks, edu-businesses and education policy: issues of evidence, expertise and influence - Thompson, Greg; Savage, Glenn; Lingard, Robert (Australian Educational Researcher, 2016)
Free to read at publisher This paper conceptualises think tanks and edu-businesses in relation to education policy work in the Australian polity. It situates the enhanced influence of both in relation to the restructured state, which has lost some key capacities in relation to the generation of research and ideas for policy. This restructuring has been strongly influenced by the techniques of new public management, the auditing of education through national and international testing and new forms of network governance, which have opened up spaces for the increased influence of think tanks and edu-businesses across the policy cycle in education. We see here the workings of a ‘polycentric state’. The paper also considers changing concepts of ‘evidence’, ‘expertise’ and ‘influence’ in respect of the involvement of think tanks and edu-businesses in circulating policy ideas and affecting policy development in Australian education. This introduction to this special issue of The Australian Educational Researcher serves as a provocation to further research on this new policy scenario.